A Study on Various Causes of Low Frequency Components in Common Mode Voltage of a Space Vector Pulse Width Modulated Three– Phase Quasi–Z–Source H–Bridge Inverter Fed from a Three–Phase Diode Bridge Rectifier - Nanda Debalina; Syam Prasid; Mukherjee Kaushik (Power Electronics and Drives)
The presence of low frequency components in the common mode voltage can cause harmful electromagnetic interference. A critical study on various causes of low frequency components in the common mode voltage of a space vector pulse width modulated Quasi–Z– source three–phase H–bridge voltage source inverter fed from a three–phase diode bridge rectifier is presented in this paper. The Quasi–Z–source network is utilized in boosting the rectified dc voltage which increases the overall voltage gain. The study considers the effect of boosting on the low frequency components. The input three-phase diode bridge rectifier has its influence in modulating the instantaneous common mode voltage and contributes low frequency components. The unbalanced three-phase supply can contribute additionally ac supply frequency component in the common mode voltage. The major contribution of this paper is the analytical, simulated and experiment-based study on various causes of the low frequency common mode voltages due to the combined action of the input non-ideal three phase grid, the front-end diode bridge rectifier as well as the load-end Z-source H-bridge three-phase inverter feeding a three-phase inductive load, while operated through a space vector pulse width modulation strategy.